Використання методу чисельно-асимптотичного наближення для дослідження процесу взаємодії β⁻-випромінювання з лінійними гнучколанцюговими полімерами - Bomba, A. Ja.; Klepko, V. V.; Klimyuk, Yu. E.; Kolupaev, B. B.; Kolupaev, B. S.; Lebedev, E. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
An algorithm for asymptotic approximation of the solution to one class of model nonlinear singularly-perturbed boundary problems in radiation physics of spatially-nonuniform linear flexible-chain polymer systems has been constructed. The obtained numerical data on the interaction of β⁻-radiation with polyvinylchloride are presented.